Understanding the Role of Adenosine A2AR Heteroreceptor Complexes in Neurodegeneration and Neuroinflammation - Borroto-Escuela, Dasiel O.; Hinz, Sonja; Navarro, Gemma; Franco, Rafael; Müller, Christa E.; Fuxe, Kjell (Frontiers in Neuroscience, 2018)
Adenosine is a nucleoside mainly formed by degradation of ATP, located intracellularly or extracellularly, and acts as a neuromodulator. It operates as a volume transmission signal through diffusion and flow in the extracellular space to modulate the activity of both glial cells and neurons. The effects of adenosine are mediated via four adenosine receptor subtypes: A1R, A2AR, A2BR, A3R. The A2AR has a wide-spread distribution but it is especially enriched in the ventral and dorsal striatum where it is mainly located in the striato-pallidal GABA neurons at a synaptic and extrasynaptic location. A number of A2AR heteroreceptor complexes exist in the striatum. The existence of A2AR-D2R heteroreceptor complexes with antagonistic A2AR-D2R interactions in the striato-pallidal GABA neurons is well known with A2AR activation inhibiting Gi/o mediated signalling of D2Rs. A2AR-mGluR5 heteroreceptor complexes were also found in with synergistic receptor-receptor interactions enhancing the inhibition of the D2R protomer signalling. They are located mainly in extrasynaptic regions of the striato-pallidal GABA neurons. Results recently demonstrated the existence of brain A2AR-A2BR heteroreceptor complexes, in which A2BR protomer constitutively inhibited the function of the A2AR protomer. These adenosine A2AR heteroreceptor complexes may modulate alpha-synuclein aggregation and toxicity through postulated bidirectional direct interactions leading to marked increases in A2AR signalling both in nerve cells and microglia. It is of high interest that formation of A2AR-A2ABR heteroreceptor complexes provides a brake on A2AR recognition and signalling opening up a novel strategy for treatment of A2AR mediated neurodegeneration.